Sociability and synapse subtype-specific defects in mice lacking SRPX2, a language-associated gene. - Breeanne M Soteros; Qifei Cong; Christian R Palmer; Gek-Ming Sia (PLoS ONE)
The FoxP2 transcription factor and its target genes have been implicated in developmental brain diseases with a prominent language component, such as developmental verbal dyspraxia and specific language impairment. How FoxP2 affects neural circuitry development remains poorly understood. The sushi domain protein SRPX2 is a target of FoxP2, and mutations in SRPX2 are associated with language defects in humans. We have previously shown that SRPX2 is a synaptogenic protein that increases excitatory synapse density. Here we provide the first characterization of mice lacking the SRPX2 gene, and show that these mice exhibit defects in both neural circuitry and communication and social behaviors. Specifically, we show that mice lacking SRPX2 show a specific reduction in excitatory VGlut2 synapses in the cerebral cortex, while VGlut1 and inhibitory synapses were largely unaffected. SRPX2 KO mice also exhibit an abnormal ultrasonic vocalization ontogenetic profile in neonatal pups, and reduced preference for social novelty. These data demonstrate a functional role for SRPX2 during brain development, and further implicate FoxP2 and its targets in regulating the development of vocalization and social circuits.